EVALUATING INJURY PATTERNS, ON-FIELD MEDICAL INTERVENTIONS, AND PREVENTIVE STRATEGIES AT THE SERDANG SEVENS RUGBY TOURNAMENT - Nazarudin, Mohamad Nizam; Wan Pa, Wan Ahmad Munsif (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The Serdang Sevens Rugby Tournament, held at Universiti Putra Malaysia, provided a valuable dataset for examining rugby injury patterns, medical interventions, and preventive strategies in a competitive setting. This study aims to analyse the prevalence, types, and mechanisms of injuries sustained during the tournament, evaluate the effectiveness of on-field medical management, and propose evidence-based injury prevention strategies tailored to the Malaysian rugby context. A retrospective observational analysis was conducted using official medical reports from the two-day tournament. The findings indicate that head and knee injuries accounted for 21% each, followed by facial and shoulder/clavicle injuries at 18% each. The most common injury types included soft tissue trauma, fractures, and concussions, with 34.5% of cases requiring hospital referrals. High-impact tackles emerged as the primary cause of injuries (70% of cases), while falls on uneven surfaces contributed to 30% of injuries. Medical interventions played a crucial role in managing injuries, with 65.5% of cases effectively treated on-site. However, the reliance on hospital referrals for severe injuries underscores the need for improved on-field diagnostic capabilities, such as portable imaging tools. The study identifies targeted warm-up routines, enhanced protective gear, and improved playing surface conditions as key preventive measures to reduce injury risks in future tournaments. The findings align with global research on rugby injuries, particularly regarding the prevalence of concussions and lower-limb injuries. However, localized factors, including field conditions and limited access to advanced medical resources, present unique challenges for Malaysian rugby. This research contributes to a growing body of knowledge on rugby injuries in Southeast Asia, offering data-driven recommendations to enhance player safety. Future studies should explore longitudinal impacts of rugby injuries and the integration of advanced diagnostic technologies, such as wearable sensors and portable ultrasound.